Approval of unit price for pile splicing - WOHA Designs PTE LTD; BUCG-ABC Joint Venture (BUCG-ABC JV); Web Structures (Brac University, 2023)
This variation order has been made between Brac University and BUCG-ABC joint venture for approval of unit price for pile spilcing of Brac University new campus project.